A Case of Torsion of the Gallbladder Suspected with SPECT-CT: Review and Recommendations. (7th January 2020) - Bergeron, Eric; Désilets, Etienne; Do, Xuan Vien; McNamara, Daniel; Chergui, Sami; Bensoussan, Michael
Abstract : Torsion or volvulus of the gallbladder is a rare situation that rapidly progresses to gangrene and linked with a poor prognosis, even death, if unrecognized and untreated. An interesting and rare case of gallbladder volvulus in which diagnosis was obtained by comparing CT images and HIDA scan with SPECT-CT is presented. Relevant literature is reviewed, and recommendations are outlined.